Representations of young people in local comic book / Roselina Musahar, Nurus Syahidah Tahreb and Norsuraya Mohd Noor - Musahar, Roselina; Tahreb, Nurus Syahidah; Mohd Noor, Norsuraya (2013)
The presence of the many comic books in today's local media scenario cannot be disputed. As such, comic books not only serve as a form of entertainment but may be a powerful source of influence to the readers especially the young ones. Being young and immature may cause problems to these young ones where whatever they read is observed to be true and have impacts on their behaviour and altitudes in real life. Whether young people are being represented in acceptable and desirable ways can be an interesting phenomenon to observe. Thus, this paper discusses the representations of young people as portrayed by the comic book artist in several issues of one of the comic books available in the local market. Findings indicate that young people are represented in several different ways that can be influential to the minds of the young ones and the perception of others about them.